KEANEKARAGAMAN JENIS TUMBUHAN PAKU TERESTRIAL DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) BANTEN - YUNITA KURNIASIH (Universitas Pasundan, 2019)
Abstract This study aims to determine the types of terrestrial ferns that exist in KHDTK (Kawasan Hutan Dengan Tujuan Khusus), the frequency and relative frequency of terrestrial ferns, the relative dominance and dominance of terrestrial ferns, the important value index of terrestrial ferns, and the dominance index of terrestrial ferns. The research method used was descriptive method with purposive sampling technique by looking at the composition of species and number of ferns in a particular area. This study was used to describe the species diversity of ferns in KHDTK (Kawasan Hutan Dengan Tujuan Khusus), Pandeglang, Banten. Observations on environmental conditions include light intensity, environmental temperature, environmental humidity, soil pH, and altitude. The results of the research obtained were the discovery of three species of ferns in KHDTK, namely Selaginella plana, Lygodium salicifolium, and Diplazium esculentum. The highest INP is found in Selaginella plana and the lowest is found in Diplazium esculentum. Selaginella plana is more dominant than other species namely Lygodium salicifolium and Diplazium esculentum.